Ֆելիքս Բախչինեանի «Հայրական» մեկնութիւնները (գրախօսութիւն «Հայրը» հատորի) - Աբրահամյան Քնարիկ / Abrahamyan Knarik (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
The review is dedicated to Felix Bakhchinyan’s novel “Father”. There are references to the manifestation of intertextuality, dialogues with other artists, which is a stable preference for the writer and is also found in previews works. («Déjà Vu. Aleppo: Valley of Love and Death”, “One Night in Ataturk’s room” and others). An attempt is made to highlight the logic of the author’s judgements about the archetype of the father, which is often based on the contrast of the mother figure. The features of the stylization of the work are also taken into account.
Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 1 .- էջ 82-85
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն